2012
DOI: 10.1063/1.4718440
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale observation of phase separation and formation of silicon clusters in Hf higk-κ silicates

Abstract: Articles you may be interested inThe effect of nanocrystallite size in monoclinic HfO 2 films on lattice expansion and near-edge optical absorption Appl. Phys. Lett. 96, 191904 (2010) Hafnium silicate films were fabricated by RF reactive magnetron sputtering technique. Fine microstructural analyses of the films were performed by means of high-resolution transmission electron microscopy and atom probe tomography. A thermal treatment of as-grown homogeneous films leads to a phase separation process. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…The aforesaid results are also coherent with our previous study of nonstoichiometric Hf-silicate materials in which we have evidenced the formation of HfO 2 and SiO 2 phases as well as Si nanoclusters (Si-ncs) upon annealing treatment [14,22]. To underline this point, we performed a TEM observation of 1,100°C annealed sample and observed a formation of crystallized Si clusters.…”
Section: Resultssupporting
confidence: 87%
“…The aforesaid results are also coherent with our previous study of nonstoichiometric Hf-silicate materials in which we have evidenced the formation of HfO 2 and SiO 2 phases as well as Si nanoclusters (Si-ncs) upon annealing treatment [14,22]. To underline this point, we performed a TEM observation of 1,100°C annealed sample and observed a formation of crystallized Si clusters.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, in the case of a bi-phased system, here composed of SiO 2 and HfO 2 , the 16 O peak origin can be different depending on the phase. One case of the HfSiO x matrix has already been studied by an atom probe [24]. It was shown that the use of the + O 2 2 form could give the compositions of the SiO 2 and HfO 2 phases that are expected in these kinds of systems.…”
Section: Apt Resultsmentioning
confidence: 99%
“…The measurement of the clusters’ composition, which can be difficult in APT volume, has been performed using the procedure developed by Vurpillot et al [30] and was recently applied by Talbot et al on similar Si nanostructured materials [18,25]. The size distribution of the Si-ncs is well fitted by a Gaussian law.…”
Section: Resultsmentioning
confidence: 99%
“…The recent improvement of this technique with the implementation of femtosecond laser pulses [24] allowed to enlarge the variety of materials to be studied. Thus, an atomic observation of photonic, solar cells, magnetic semiconductor, or nanoelectronic devices is now available [18,19,25-28]. The Er-SRSO film with the shape of a tiny needle, required for APT analyses, was prepared using a focused ion beam annular milling procedure.…”
Section: Methodsmentioning
confidence: 99%